The Influence of Own Working Capital and Investment Working Capital on Economic Profitability at the Teratai Cooperative of the Lahat Police - Deya Okta Sari; Darwin Kesuma; Mujari Mujari (Universitas Dehasen Bengkulu, 2026)
The purpose of this study is to determine the effect of equity working capital on economic profitability at the Teratai Cooperative, Lahat Police Resort. To determine the effect of investment working capital on economic profitability at the Teratai Cooperative, Lahat Police Resort. To determine the joint effect of equity working capital and investment working capital on economic profitability at the Teratai Cooperative, Lahat Police Resort. The sample used was data on equity working capital, investment working capital, and economic profitability at the Teratai Cooperative, Lahat Police Resort from 2022 to 2024. The results showed that equity working capital significantly influenced economic profitability at the Teratai Cooperative, Lahat Police Resort. Investment working capital did not significantly influence economic profitability at the Teratai Cooperative, Lahat Police Resort. Both equity working capital and investment working capital significantly influenced economic profitability at the Teratai Cooperative, Lahat Police Resort.